Russian-Ukraine War and its Impact on the European Economy - Williams, Precious Mary; Ade-Ibijola, Aderemi Opeyemi; Opeyeoluwa, Rotimi Olajide (African Journal of Stability and Development (AJSD), 2024)
This study examines the impact of the Russian-Ukraine war on the economy of Europe, concentrating on trade disruptions, energy security, foreign direct investment (FDI) flows, and the socioeconomic ramifications of the war[1]induced refugee crisis. This study employs the descriptive research design, qualitative research method and a secondary source of data collection. The research uncovers the problems and possibilities coming from the war, as well as the larger implications for economic growth, development, and stability in the area. The results reveal severe interruptions to commercial links between European nations, especially Russia, and Ukraine, with key sectors such as energy, manufacturing, and agriculture facing considerable disruptions. Energy security emerges as a significant worry, spurring attempts to diversify energy sources and lessen dependence on Russian supply. Meanwhile, the war has resulted in a drop in FDI inflows to Russia and Ukraine, aggravating economic concerns in both nations and hurting their growth prospects. Furthermore, the research shows the burden on social welfare systems in European nations hosting migrants, since the inflow of refugees exerts great demands on resources and capabilities. Investments in housing, health care, education, and social welfare are vital for satisfying the different needs of displaced people and facilitating their long-term integration into society. However, issues connected to social cohesiveness, community connections, and political dynamics within host nations also occur. The study recommends diplomatic resolution of the dispute through peaceful discussions, involving European Union (EU) member states- Russia, Ukraine, and other parties. This could involve neutral mediation, de-escalating initiatives, and confidence-building measures.